ASPECTOS SÓCIO-DEMOGRÁFICOS E DE SAÚDE EM MULHERES PÓS-MENOPAUSA DO MUNICÍPIO DE CATUÍPE-RS - Bertolo, Elvio M.; Leite, Marinês T.; Berlezi, Evelise M.; Batistti, Iara D. E.; Franco, Rosecler R.; Bottaro, Silvania M. (Salão do Conhecimento, 2013)
Resumo